The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1990
DOI: 10.1073/pnas.87.3.955
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of human protein 4.2: a major component of the erythrocyte membrane.

Abstract: Protein 4.2 (P4.2) comprises -5% of the protein mass of human erythrocyte (RBC) membranes. Anemia occurs in patients with RBCs deficient in P4.2, suggesting a role for this protein in maintaining RBC stability and integrity. We now report the molecular cloning and characterization of human RBC P4.2 cDNAs. By immunoscreening a human reticulocyte cDNA library and by using the polymerase chain reaction, two cDNA sequences of 2.4 and 2.5 kilobases (kb) were obtained. These cDNAs differ only by a 90-base-pair inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…The most 5' sequences of the two transcripts obtained were identical (verifying that they are derived from a single gene) and extended to nucleotide -214, numbering backwards from the translation start site. However, this position was 12 nucleotides downstream of the most 5' sequence generated by Sung et al (7), which extended to nucleotide -226. This apparent difference in the 5' origin of the band 4.2 transcript likely reflects a slight degradation of our reticulocyte RNA and in the following discussion we assume that the transcription start site is at nucleotide -226 (marked by an arrow in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most 5' sequences of the two transcripts obtained were identical (verifying that they are derived from a single gene) and extended to nucleotide -214, numbering backwards from the translation start site. However, this position was 12 nucleotides downstream of the most 5' sequence generated by Sung et al (7), which extended to nucleotide -226. This apparent difference in the 5' origin of the band 4.2 transcript likely reflects a slight degradation of our reticulocyte RNA and in the following discussion we assume that the transcription start site is at nucleotide -226 (marked by an arrow in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…6; see also ref. 7). We found that the amino acid sequence of human erythrocyte band 4.2 has homology with two transglutaminases, guinea pig liver transglutaminase, and the a subunit of human coagulation factor XIII.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…On the carboxy-terminal side, aromatic residues are usually present, except for a Cys residue in human TGase 4 (Grant et al, 1994). The enzymatically inactive P4.2 isoform has an aromatic residue (Sung et al, 1990) at the amino-terminal and negatively charged residues at the carboxyterminal sides. The essential catalytic active site Cys-272 residue is located just downstream of Arg268-Tyr269, which explains the high degree of conservation in the enzymatically active isoforms.…”
Section: The Function Of Cis Peptide Bonds In Tg Asementioning
confidence: 99%
“…The transamidating function of the protein seems to be switched to that of receptor signaling. The membrane-skeletal protein, band 4.2, of human erythrocytes also contains sequence similarities near the active center region of TGases without, however, containing the catalytically important cysteine residue of the enzyme (51,52). No cross-reacting antibodies for the 4.2 protein and TGase have been reported.…”
mentioning
confidence: 99%